2006
DOI: 10.4049/jimmunol.176.3.1561
|View full text |Cite
|
Sign up to set email alerts
|

TLR Agonists Abrogate Costimulation Blockade-Induced Prolongation of Skin Allografts

Abstract: Costimulation blockade protocols are effective in prolonging allograft survival in animal models and are entering clinical trials, but how environmental perturbants affect graft survival remains largely unstudied. We used a costimulation blockade protocol consisting of a donor-specific transfusion and anti-CD154 mAb to address this question. We observed that lymphocytic choriomeningitis virus infection at the time of donor-specific transfusion and anti-CD154 mAb shortens allograft survival. Lymphocytic choriom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(154 citation statements)
references
References 70 publications
8
144
0
Order By: Relevance
“…We and others have previously shown that the administration of single TLR agonists can prevent the induction of cardiac transplantation tolerance or of long-term skin allograft acceptance by anti-CD154/DST (15)(16)(17). However, several pieces of evidence indicate that the mechanisms by which TLR ligands and LM prevent transplantation tolerance can be distinct.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We and others have previously shown that the administration of single TLR agonists can prevent the induction of cardiac transplantation tolerance or of long-term skin allograft acceptance by anti-CD154/DST (15)(16)(17). However, several pieces of evidence indicate that the mechanisms by which TLR ligands and LM prevent transplantation tolerance can be distinct.…”
Section: Discussionmentioning
confidence: 95%
“…This is thought to occur via direct activation of cross-reacting alloreactive T cells by viral Ags (7,9) or upon bystander activation of allospecific T cells (9,12). We and others have also shown that engagement of single TLRs, receptors that recognize molecular patterns expressed by viruses, fungi, parasites, and bacteria, is sufficient to prevent transplantation tolerance by anti-CD154 mAb (15)(16)(17). Conversely, elimination of the TLR adaptor MyD88 facilitated the induction of transplantation tolerance to skin allografts (15,17).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 99%
“…Conversely, other studies show that despite costimulatory receptor blockade, challenge with TLR agonists such as LPS and CpG DNA at the time of allotransplantation prevents tolerance induction (52,54). Using donor-specific transfusion and CD154 Ab with a one-time TLR agonist challenge, Thornley et al (54) found that blockade of skin graft tolerance induction by TLR stimulation was associated with prevention of alloreactive CD8 ϩ T cell apoptosis.…”
Section: Examining Prr Signaling In Allotransplantationmentioning
confidence: 99%
“…Using donor-specific transfusion and CD154 Ab with a one-time TLR agonist challenge, Thornley et al (54) found that blockade of skin graft tolerance induction by TLR stimulation was associated with prevention of alloreactive CD8 ϩ T cell apoptosis. Moreover, Chen et al (52) found that blockade of heart graft tolerance induction by administering CpG DNA along with CD154 Ab occurred in conjunction with a reduced ratio of Tregs to effector T cells at the graft site.…”
Section: Examining Prr Signaling In Allotransplantationmentioning
confidence: 99%
“…TLR activation, however, provokes an inflammatory response, cytokine secretion, and APC maturation that is independent of the interaction between CD154 and CD40 (1). We have previously shown that TLR activation can bypass costimulation blockade, activate adaptive immunity, and impair allograft survival (13).…”
Section: Type 1 Ifn Mediates Cross-talk Between Innate and Adaptive Imentioning
confidence: 99%